Меню

УСЛОВИЕ:

1. Преобразуйте в многочлен:
а) (а – 2)( а + 2) – 2а(5 – а)
б) (у – 9)2 – 3у(у + 1)
в) 3(х – 4) 2 – 3х2

2. Разложите на множители:
а) 25х – х3 б) 2х2 – 20х + 50

3. Найдите значение выражения а2 – 4bс, если а = 6, b = -11, с = -10
а) 452 б) -202 в) -404 г) 476

4. Упростите выражение:
(с2 – b)2 – (с2 - 1)(с2 + 1) + 2bс2

5. Докажите тождество:
(а + b)2 – (а – b)2 = 4аb



РЕШЕНИЕ:

Преобразуйте в многочлен:
 а) (а – 2)( а + 2) – 2а(5 – а) =а^2-4-10a+2a^2=6a^2-10a-4
 б) (у – 9)2 – 3у(у + 1) =y^2-18y+81-3y^2-3y=-2y^2-21y+81
 в) 3(х – 4) 2 – 3х2 =3(x^2-8x+16)-3x^2=3x^2-24x+48-3x^2=48-24x
2. Разложите на множители:
 а) 25х – х3=x(25-x^2)=x(5-x)(5+x)

 б) 2х2 – 20х + 50 =2(x^2-10x+25)=2(x-5)^2=2(x-5)(x+5)
 3. Найдите значение выражения а2 – 4bс=36-4*(-11)*(-10)=36-440=-404
 а) 452 б) -202 в) -404 г) 476 
4. Упростите выражение:
 (с2 – b)2 – (с2 - 1)(с2 + 1) + 2bс2 =c^4-4bc^2+b^2-c^4+1=-4bc^2+b^2+1
5. Докажите тождество:
(а + b)2 – (а – b)2 = 4аb

a^2+2ab+b^2-a^2+2ab-b^2=2a+2ab=4ab 

2. а/ (5-х) х*(х+5); б/ 2(x-5)^2;

4. b^2+1.






Похожие примеры: